2013
DOI: 10.1002/ppul.22887
|View full text |Cite
|
Sign up to set email alerts
|

The use of convex probe endobronchial ultrasound-guided transbronchial needle aspiration in a pediatric population: A multicenter study

Abstract: We report the first multicenter study to date confirming the feasibility and utility of EBUS-TBNA in the pediatric population. Due to the low overall procedural risk of EBUS-TBNA, it should be considered as a potential first line diagnostic option for children presenting with mediastinal or hilar abnormalities but further prospective studies are needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
62
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(63 citation statements)
references
References 39 publications
0
62
0
1
Order By: Relevance
“…There were only three patients less than 18 years old. However, Gilbert et al (7) confirmed that it was feasible for pediatric patients who underwent EBUS-TBNA. There were 83 (9.8%) patients more than 70 years old who stayed safe with EBUS-TBNA.…”
Section: Puncture Resultsmentioning
confidence: 94%
“…There were only three patients less than 18 years old. However, Gilbert et al (7) confirmed that it was feasible for pediatric patients who underwent EBUS-TBNA. There were 83 (9.8%) patients more than 70 years old who stayed safe with EBUS-TBNA.…”
Section: Puncture Resultsmentioning
confidence: 94%
“…Adequate sampling can be achieved in 95% of cases, although diagnostic yield may only be 47%. The complication rate in children appears to be very low [65][66][67][68].…”
Section: Discussionmentioning
confidence: 99%
“…Although a 6.9-mm diameter puncturescope can be passed through a 2.5 laryngeal mask airway (LMA), ventilation is limited and a 4.0 LMA is preferable. EBUS TBNA can be performed under either general anaesthesia or sedation, and is generally well tolerated in children aged ⩾9 years [68]. Adequate sampling can be achieved in 95% of cases, although diagnostic yield may only be 47%.…”
Section: Discussionmentioning
confidence: 99%
“…Gilbert et al 2 reviewed 21 paediatric patients who underwent EBUS TBNA using a specially designed bronchoscope equipped with a distal ultrasound probe allowing real-time ultrasound imaging at the time of biopsy (performed via operating channel). No significant adverse events were reported.…”
Section: Shivanthan Shanthikumar (Respiratory Fellow) and Jo Harrisonmentioning
confidence: 99%
“…There was no difference in diagnostic yield between EBUS TBNA and EUS-B-FNA with a calculated diagnostic sensitivity of 79.1% for EBUS TBNA or EUS-B-FNA. One issue with EBUS TBNA identified in adults is the relatively high false-negative rate of needle aspirates in diagnosing lymphomas with prominent fibrosis and a mixed cellular population 2. This limitation is important to take into account in paediatric practice, given the higher incidence of lymphoma.…”
Section: Shivanthan Shanthikumar (Respiratory Fellow) and Jo Harrisonmentioning
confidence: 99%